ANALISIS ORIENTASI PASAR, TINGKAT UTANG, DAN LITERASI KEUANGAN TERHADAP KINERJA KEUANGAN UMKM DI KOTA BATAM - Oktivia; L. Tobing, Vargo Christian (SCIENTIA JOURNAL, 2025)
MSMEs play an important role in the Indonesian economy, especially in creating jobs and driving economic growth. However, MSMEs often face obstacles in managing financial performance, including recording and managing debt. This study aims to analyze the effect of market orientation, debt levels, and financial literacy on the financial performance of MSMEs in Batam City. The method used is a quantitative approach, with data collection through Google Form. The sample uses the Slovin formula calculation and the statements in the questionnaire use a Likert scale. The population of this study were micro-entrepreneurs registered with the Batam City Cooperative Office as many as 275 people, with a sample of 163 MSMEs. The results showed that market orientation, debt levels, and financial literacy significantly affect the financial performance of MSMEs